PERTAGGUNGJAWABAN PIDANA PELAKU TINDAK PIDANA MEMPERDAGANGKAN JARINGAN TUBUH MANUSIA MENURUT HUKUM POSITIF DI INDONESIA - Panca Sarjana Putra (Universitas Islam Sumatera Utara, 2023)
The perpetrators of the crime of trafficking in human organs are not only carried out by criminal syndicates who want to get money by illegal means, but the perpetrators can also be the people themselves who sell their organs with the intent and purpose of getting money. Regulations regarding the criminal act of trading in organs/body tissues in the Criminal Code do not clearly prohibit acts of trading in human organs, as well as in Law Number 21 of 2007 concerning the Eradication of Trafficking in Persons which includes trading in organs into acts of exploitation of people while in the Law -Law Number 36 of 2009 concerning Health has clearly regulated that human organs are prohibited from being traded under any circumstances. Article 192 of Law Number 36 of 2009 stipulates that every person who deliberately trades organs or body tissue under any pretext as referred to in Article 64 paragraph (3) is subject to criminal sanctions. with a maximum imprisonment of 10 years and a maximum fine of IDR 1 billion. Keywords: Criminal Acts, Trading, Body Organs